Prophylactic self-medication and bacterial avoidance behaviours in Arctia plantaginis larvae - Murphy, Liam M. (2017)
Insects have a range of behavioural defences that they can use against parasites. One of these behaviours is self-medication: the use of biologically active compounds by the host to ameliorate the effects of parasites and diseases. Another intuitive behaviour would be to avoid infection risks if they are recognisable in the environment. However prophylactic self- medication (performing self-medication before the infection has occurred) has not yet been reported or proven conclusively in insects, and avoidance of parasites has limited examples in the literature. In this experiment, I studied if the polyphagous lepidopteran, Arctia plantaginis, practised prophylactic self-medication by changing their diet choice when exposed to a high infection risk caused by infected corpses of conspecifics in their environment. I expect the larvae to recognise higher infection risks, and so respond by consuming a diet with more dandelion that has previously been shown to give higher survival for infected larvae. Larvae were maintained individually in either a high infection risk, a low infection risk, and no infection risk environments. The larvae’s choice of dandelion or plantain leaves, in response to one of these three different levels of infection risk, was observed over a nine-day period. I also studied whether the larvae of this species could recognise and avoid potentially pathogenic bacteria in their environment. I expected the larvae to avoid infected leaves and feed predominantly on control leaves. The larvae in this experiment had to choose between leaves infected with Serratia marcescens or uninfected, control leaves. It was found that the larvae did not choose uninfected leaves over infected leaves, so they did not avoid the free-living pathogenic bacteria. However, they did alter their diet choice, consuming significantly more dandelion than larvae in other treatment groups, in response to the presence of conspecifics’ corpses that had been killed by the pathogen. The presence of an uninfected conspecifics corpse did not elicit the same behavioural response. These larvae seem to engage in prophylactic consumption after consuming medicative substances earlier in life, and this is the first claim for non-social insects to use this behavioural defence against parasites or pathogens. This behaviour could be more widespread among insects, especially polyphagous species and show that behavioural defences play a big part in insect – parasite interactions.